2009
DOI: 10.12702/1984-7033.v09n04a05
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and stability of carotenoids in maize cultivars

Abstract: - Eberhart and Russell (1966), Lin and Binns (1988) and Rocha et al. (2005) were used to analyze adaptability and stability. In general, the linear regression model proposed by Eberhart and Russell (1966)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
2
1
6
Order By: Relevance
“…Similar results have been reported by Cardoso et al (2009), Rios et al (2009), andEgesel et al (2003a). When the entries were divided into diallel hybrids and local checks, the local checks did not show significant differences in grain yield and b-cryptoxanthin and a-carotene contents.…”
Section: Resultssupporting
confidence: 87%
“…Similar results have been reported by Cardoso et al (2009), Rios et al (2009), andEgesel et al (2003a). When the entries were divided into diallel hybrids and local checks, the local checks did not show significant differences in grain yield and b-cryptoxanthin and a-carotene contents.…”
Section: Resultssupporting
confidence: 87%
“…Rios et al (2009) , taken as a reference for comparisons (Weber, 1987;Kurilich and Juvik, 1999;Hulshof et al, 2007), were above and below the values found in the present work.…”
Section: Resultscontrasting
confidence: 56%
“…Among these is the method proposed by Eberhart and Russell (1966), based on linear regression analysis, which among its advantages includes ease of application and interpretation of results. The recommendation of maize cultivars based on this method has been successfully employed by several authors (CARGNELUTTI FILHO et al, 2009;MIRANDA et al, 2009;OLIVEIRA;MOREIRA;FERREIRA, 2013;RIOS et al, 2009;SCAPIM et al, 2010), and recently, Carvalho et al (2014) used this method to study the adaptability and stability of 16 maize genotypes in the state of Tocantins, and classify them as to production objective: either grain or green weight.…”
Section: Introductionmentioning
confidence: 99%